Welcoming with risk classification in teaching hospitals: assessment of structure, process and result (Revista Latino-Americana de Enfermagem, 2013)
OBJECTIVE: to assess, from the worker's viewpoint, the structure, the process and the results of the Emergency Hospital Services that have taken up the guideline of "Welcoming with Risk Classification" in two teaching hospitals of the state of Paraná. METHOD: quantitative and descriptive research, exploratory and prospective, using random sampling stratified by professional category, comprising a universe of 216 professional people. RESULTS: they found some points of agreement regarding the promotion of a welcoming and humane environment; privacy and security; welcome and shelter of the companion and also the sheltering and classification of all patients; however, there was disagreement about the comfort of the environment, reference system and counter-reference, prioritisation of seriously ill patients in post-classification service, communication between the members of the multi-professional team and reassessment of the guideline. CONCLUSION: the workers assess the development of the guideline as being precarious, due mainly to the lack of physical structure, due to the lack of physical structure and shortcomings in the service process.